SISTEM KATA ULANG BAHASA JAWA SUBDIALEK MADIUN - Yani Paryono (Madah: Jurnal Bahasa dan Sastra, 2014)
The study that entitled The Repetition Words System of Javanese Language Madiun Subdialect aims to describe the morphological system of words repetition  of Javanese language  in Madiun Regency. The collection data of this qualitative research is by using the technique of tapping and recording, observing and taking notes, as well as interviewing techniques. The research data was obtained from the speech of Javanese from the Javanese speakers in Ngawi in the form of questionnaires and speech loose when making observations. The results obtained in this study are the repetition of Javanese word  Madiun subdialect. Madiun subdialect uses many vowels and consonants of standard Javanese language, especially Mataraman Javanese although  are some phonemes are that affected by    Suroboyoan language.